2021
DOI: 10.29219/fnr.v65.5589
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic effect of fructose on normal rats in a mild dose with glucose and saccharose as control

Abstract: Aims: To study the metabolic effects of fructose, glucose and saccharose in a moderate dose by analyzing changes of blood indicators, pancreas inflammation, liver fat accumulation and intestinal microbiota in normal Sprague-Dawley (SD) rats. Subjects and methods: Six-week-old rats were assigned to four groups (n = 10), which were gavaged with normalsaline (Con), glucose dissolved in normal saline (Glu), saccharose-glucose dissolved in normal saline (Sac), and fructose dissolved in normal saline (Fru) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The effect on LCA may be partly attributable to the higher relative abundance of Lactobacillus after the consumption of sugar-enriched diet, which has been reported to participate in the conversion of primary bile acids to secondary bile acids . Previous studies have reported that dietary fiber increases fecal concentrations of propionic acid and butyric acid, while diet enriched in added sugars decreases fecal butyric acid concentrations in animal models . However, with the use of an isocaloric substitution model, we found that carbohydrate type had little effect on fecal concentrations of SCFAs, which is consistent with prior work …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect on LCA may be partly attributable to the higher relative abundance of Lactobacillus after the consumption of sugar-enriched diet, which has been reported to participate in the conversion of primary bile acids to secondary bile acids . Previous studies have reported that dietary fiber increases fecal concentrations of propionic acid and butyric acid, while diet enriched in added sugars decreases fecal butyric acid concentrations in animal models . However, with the use of an isocaloric substitution model, we found that carbohydrate type had little effect on fecal concentrations of SCFAs, which is consistent with prior work …”
Section: Discussionsupporting
confidence: 91%
“…60 Previous studies have reported that dietary fiber increases fecal concentrations of propionic acid and butyric acid, 61 while diet enriched in added sugars decreases fecal butyric acid concentrations in animal models. 62 However, with the use of an isocaloric substitution model, we found that carbohydrate type had little effect on fecal concentrations of SCFAs, which is consistent with prior work. 26 In summary, with the use of an isocaloric substitution model, the results of the current study demonstrated that in comparison to WG-enriched diet, the consumption of both sugar-and RGenriched diets resulted in higher fasting plasma LDL-C and HDL-C concentrations, and sugar-enriched diet resulted in higher TC, non-HDL-C, VLDL-C, and TG concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous research, we found that low fructose intake did not influence metabolic effects 17 , while high fructose diet induced inflammatory response and mucus impairment 18 . Therefore, this study aimed to find potential mechanisms of mucus impairment and dysfunction induced by a high fructose diet.…”
Section: Discussion/ Conclusionmentioning
confidence: 85%
“…For goblet cells counting, 5 µm thickness and carnoy-fixed sections (60% methanol, 30% chloroform, 10% acetic acid) were stained using the Alcian Blue-Periodic Acid Schiff (AB-PAS) method according to the manufacturer's instructions (Solarbio, Beijing, China). Briefly, sections were incubated with a 1% Alcian blue solution (pH 2.5) in 3% acetic acid solution for (15)(16)(17)(18)(19)(20) minutes. The slides were then rinsed in distilled water for two minutes and oxidized in 0.5% periodic acid solution for 5 minutes.…”
Section: Histological Analysismentioning
confidence: 99%
“…Microbiome profiles enriched with Porphyromonadaceae have previously been associated with lower levels of VAT in a small cohort of older adults [ 22 ]. In another study, increased abundance of Peptostreptococcaceae has been associated with nonalcoholic fatty liver disease [ 23 ] and, in rat models, with reduced lifespan [ 24 ] and increased fasting and postprandial blood glucose values and liver fat accumulation [ 25 ]. These taxa likely play a role as adiposity modulators through the production of short-chain fatty acids, and in particular, a higher abundance of Porphyromonadaceae has been associated with higher levels of acetate, n-Butyrate, and propionate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%